PRELIMINARY STUDY OF THE NUTRITIONAL COMPOSITION OF THE EDIBLE MUSHROOM Pleurotus ostreatus GROWN IN COFFEE PULP - Nieto Juárez, Jessica I. (2019)
This research work aims to obtain a nutritious and protein food by growing of edible mushrooms from agricultural and industrial waste, being the coffee pulp a potential waste for this purpose, in order to improve public and environmental health, thus reducing the pollution that these solid waste generate. The nutritional composition of the edible mushroom Pleurotus ostreatus grown in coffee pulp was studied as a quality control for its human consumption. The edible mushroom was obtained by the biotransformation of the lignocellulosic solid waste (coffee pulp), i.e. solid-state fermentation. The waste of coffee pulp was supplied by coffee farmers from the Department of Amazonas (Peruvian Rainforest) and Piura (Peruvian Highlands). The results showed that the content of macro and micronutrients in the oyster mushroom grown in coffee pulp from the department of Amazonas and Piura were similar. The content of crude protein, in dry sample, was of 28,6 % and 29,7 % respectively, with a high-water content (~ 86 %) and a low content of carbohydrates (< 8%) and fats (< 1%), in fresh sample. The micronutrient content was mostly potassium, followed by calcium, magnesium, sodium and traces of iron. The content of caffeine in the oyster mushroom was less than 10 µg/g in dry sample. Therefore, this indicates that the oyster mushroom grown on coffee pulp waste is highly nutritious and healthy, which could be included in the daily diet to improve people’s health, nutrition and control diseases.